Developmentally regulated autophagy is required for eye formation in Drosophila. - Billes, V.; Kovács, T.; Manzéger, A.; L?rincz, P.; Szincsák, S.; Reg?s, Á.; Kulcsár, P.I.; Korcsmáros, T.; Lukácsovich, T.; Hoffmann, G.; Erdélyi, M.; Mihály, J.; et al. (Autophagy, 2018)
The compound eye of the fruit fly Drosophila melanogaster is one of the most intensively studied and best understood model organs in the field of developmental genetics. Herein we demonstrate that autophagy, an evolutionarily conserved selfdegradation process of eukaryotic cells, is essential for eye development in this organism. Autophagic structures accumulate in a specific pattern in the developing eye disc, predominantly in the morphogenetic furrow (MF) and differentiation zone. Silencing of several autophagy genes (Atg) in the eye primordium severely affects the morphology of the adult eye through triggering ectopic cell death. In Atg mutant genetic backgrounds however genetic compensatory mechanisms largely rescue autophagic activity in, and thereby normal morphogenesis of, this organ. We also show that in the eye disc the expression of a key autophagy gene, Atg8a, is controlled in a complex manner by the anterior Hox paralog Lab (Labial), a master regulator of early development. Atg8a transcription is repressed in front of, while activated along, the MF by Lab. The amount of autophagic structures then remains elevated behind the moving MF. These results indicate that eye development in Drosophila depends on the cell death-suppressing and differentiating effects of the autophagic process. This novel, developmentally regulated function of autophagy in the morphogenesis of the compound eye may shed light on a more fundamental role for cellular self-digestion in differentiation and organ formation than previously thought.